Melatonin Accelerates Osteoporotic Bone Defect Repair by Promoting Osteogenesis–Angiogenesis Coupling - Zheng, Sheng; Zhou, Chunhao; Yang, Han; Li, Junhua; Feng, Ziyu; Liao, Liqing; Li, Yikai (Frontiers in Endocrinology, 2022)
Previous studies have revealed that melatonin could play a role in anti-osteoporosis and promoting osteogenesis. However, the effects of melatonin treatment on osteoporotic bone defect and the mechanism underlying the effects of melatonin on angiogenesis are still unclear. Our study was aimed to investigate the potential effects of melatonin on angiogenesis and osteoporotic bone defect. Bone marrow mesenchymal stem cells (BMSCs) were isolated from the femur and tibia of rats. BMSCs osteogenic ability was assessed using alkaline phosphatase (ALP) staining, alizarin red S (ARS) staining, qRT-PCR, western blot and immunofluorescence. BMSCs-mediated angiogenic potentials were determined using qRT-PCR, western blot, ELISA, immunofluorescence, scratch wound assay, transwell migration assay and tube formation assay. Ovariectomized (OVX) rats with tibia defect were used to establish osteoporotic bone defect model and then treated with melatonin. The effects of melatonin treatment on osteoporotic bone defect in OVX rats were analyzed using micro-CT, histology, sequential fluorescent labeling and biomechanical test. Our study showed that melatonin promoted both osteogenesis and angiogenesis in vitro. BMSCs treated with melatonin indicated higher expression levels of osteogenesis-related markers (ALP, OCN, RUNX2 and OSX), and angiogenesis-related markers (VEGF, Ang-2 and Ang-4)，compared to un-treated group. Significantly, melatonin was not able to facilitate human umbilical vein endothelial cells angiogenesis directly, but it possessed the ability to promote BMSCs-mediated angiogenesis by upregulating VEGF levels. In addition, we further found that melatonin treatment increased bone mineralization and formation around the tibia defect in OVX rats, compared with control group. Immunohistochemical staining indicated higher expression levels of osteogenesis-related marker (OCN) and angiogenesis-related markers (VEGF and CD31) in the melatonin-treated OVX rats. Then, it showed that melatonin treatment also increased bone strength of tibia defect in OVX rats, with increased ultimate load and stiffness, performed by three-point bending test. In conclusion, our study demonstrated that melatonin could promote BMSCs-mediated angiogenesis and promote osteogenesis-angiogenesis coupling. We further found that melatonin could accelerate osteoporotic bone repair by promoting osteogenesis and angiogenesis in OVX rats. These findings may provide the evidence for the potential application of melatonin in osteoporotic bone defect.